The impact of chronic intermittent hypoxia on the expression of intercellular cell adhesion molecule-1 and vascular endothelial growth factor in the ischemia-reperfusion rat model - Yang, Meili; Chen, Yafang; Wu, Zhengang; Zhang, Yaping; Cai, Ruowei; Ye, Lichao; Huang, Yinhui; Wang, Lingxing; He, Huiling (Folia Neuropathologica, 2018)
The aim of this study was to investigate the effect and mechanism of chronic intermittent hypoxia (CIH) on cerebral injury using the ischemia-reperfusion rat model. In total, 36 SD rats were divided into three groups: pseudo-surgery group (sham group), ischemia-reperfusion (IR) group (CIR group), and CIH intervention group (CIH group). The IR model was established using the suture-occluded method. CIH intervention was performed starting at 12 weeks prior to the establishment of the IR model for rats in the CIH group. Ultra-microstructure was examined using an electron microscope. Expression of intercellular cell adhesion molecule-1 (ICAM-1) and vascular endothelial growth factor (VEGF) in rat brain tissue was evaluated by immunohistochemical methods and western blot assays. The neurological deficit scores of rats in the CIH group were higher than those in the CIR group (p < 0.05). Using electron microscopy, we observed more severe edema around the capillaries of the rat brain that resulted in more pressure on the vascular wall of the capillaries in the CIH group compared to the CIR group. The expression of ICAM-1 and VEGF in rat brain tissue was rare in the sham group, but was significantly elevated in the CIR group (p < 0.05) and even higher in the CIH group, compared to the CIR group. Hence, the brain injury in ischemia-reperfusion rat models following CIH intervention may be related to the increased expression of ICAM-1 and VEGF.